The motives of Palestinian journalists ' reluctance to practice investigative journalism - Fatafta, Omar Issa (Arab Journal for Sciences and Research Publishing, 2021)
The study aims to identify the motives of journalists' reluctance to practice investigative journalism. The researcher relies on the method of codified interview and questionnaire in order to identify the main motives that prevent journalists from practicing investigative journalism and to analyse the motives in depth after collecting sufficient information.The study uses the descriptive research method, which is concerned with studying the current facts related to the nature of a particular phenomenon, a specific situation, or a group of events. The method aims to obtain sufficient information and gives an accurate description of the phenomenon studied.The study population is the Palestinian journalists registered at the Palestinian Journalists Syndicate (PJS) in the West Bank, and they totalled at (1200) journalists on 15 January 2020.The research sample was chosen randomly. The researcher could reach Journalists working in the West Bank. The total number of the distributed questionnaires was 126; 120 copies were collected, and 6 were excluded.The study showed that the different political trends in Palestinian society and the editorial policies pursued by the media are among the most prominent reasons that have led to the reluctance of journalists to practice investigative journalism. The study also found that the regulations and laws in force within press institutions, in addition to the lack of support and funding for institutions, have limited producing more investigations recently.
Keywords: Apathy; Palestinian journalists; Investigative journalism